Indoor mobility challenges among older adults: A systematic review of barriers and limitations - Xin Er Yaw; Pei Lee Teh; Weng Marc Lim; Shaun Wen Huey Lee (PLoS ONE, 2025)
Introduction The global population is projected to double by 2050 with most older adults expressing preference to age in place. Despite this demographic shift, indoor mobility challenges which directly impact independence, safety and quality of life remains poorly understudied, creating a critical knowledge gap for effective intervention development. Methods A systematic literature search was conducted on four databases from inception to September 2024. Inclusion criteria included: (1) participants aged 60 years and above; (2) were primary data on self-reported indoor mobility challenges; and (3) published in English language. Two reviewers independently performed data abstraction, evaluated the risk-of-bias and quality of included article using the NewCastle Ottawa Scale for cross-sectional or Joanna Briggs Institute Checklist for qualitative studies. Thematic synthesis with constant comparison analysis identified key mobility constraint factors. Results Nine studies encompassing 1,833 participants were identified. Older adults reported four main indoor mobility challenges: fatigability, poor balance, home environmental barriers, reduced strength and limb weakness. These limitations contributed to reduced endurance, even in indoor settings. The presence of various health conditions further compromised their mobility and ability to age in place healthily. Conclusion To support ageing in place, a comprehensive environmental assessments and home modifications can be considered. Multi-stakeholder collaborations are needed to support the independence, safety, and quality of life of older adults who wish to age in place. Further research is warranted in suburban and rural areas to explore socioeconomic factors and determinants of indoor mobility.